Rare Case of Malignant Insulinoma Treated with Chemoembolization and Bland Embolization - Nazanin Sheikhan; Joshua Hardy; George Trad; Andrew Nguyen; Andrey Manov (Research Highlights in Disease and Health Research Vol. 9, 2023)
This chapter described a rare case of a patient with unusual presentation of malignant insulinoma. The patient presented with right upper quadrant abdominal pain and diarrhea for 3 weeks which have worsened in the last 4- days. Also the patient had episodes of confusion in the last one month. His blood glucose was never checked at that time. The patient did not have the classical presentation of Insulinoma with the Whipple’s triad- measured fasting blood glucose less than 50 mg/dl, symptoms of hypoglycemia at the time of low plasma blood glucose and immediate relieve of the symptoms after the administration of intravenous glucose. The diarrhea is not a usual feature of Insulinoma although frequently happens in other neuroendocrine tumors like gastrinoma, VIP secreting neuroendocrine tumors, glucagonoma etc. CT of the abdomen which was done because of the patient symptoms revealed 6sm mass in the tail of the pancreas, with thrombosis of the splenic vein and multiple metastasis of the pancreatic mass to the liver. Our initial though was that the patient has metastatic adenocarcinoma of the pancreas. The endoscopic ultrasound (EUS) of the pancreas was done with fine needle aspiration of the pancreatic mass which showed the presence of the neuroendocrine tumor. During the work up of the pancreatic mass we performed 72- hour fasting test which revealed low plasma blood glucose less than 55 mg/dl, increased at that time C- peptide, pro-insulin and Insulin levels and negative screening for sulfonylureas medications or glinides. Anti- insulin antibody test was negative as well as Pro- IGF-2. Injection of Glucagon 1 mg intravenously let to increment of the blood glucose more than 25 mg/dl in 30 minutes. Beta-hydroxybutyrate level was less than 2.7 nmol/l. All this pointed out towards endogenous hyperinsulinemia in the context of the presentation due to pancreatic insulinoma. This together with the EUS and radiological results suggested the presence of malignant insulinoma. Thereafter the surgical team was consulted. They performed exploratory laparotomy with distal pancreatectomy, splenectomy, cholecystectomy, and appendectomy and biopsy of the liver lesions and spleen. Surgical pathology specimen of the spleen and liver was consistent with a well-differentiated neuroendocrine tumor similar to that from the pancreatic lesion. The patient was treated with surgical resection of the distal pancreas when the insulinoma was located, splenectomy, cholecystectomy and appendectomy. Also, chemoembolization and bland embolization of the metastatic tumors of the liver were done and patient’s hypoglycemia was treated with Diazoxide and short course of Steroids and Octreotide. We are describing this patient to emphasize the need of broad differential diagnosis of the pancreatic lesions presenting only with abdominal pain, diarrhea and intermittent confusion without any measurement of the blood glucose. What looked like classical metastatic adenocarcinoma of the pancreas turned out to be atypical presentation of one of the Neuroendocrine tumors- Insulinoma. Also only 10% of Insulinomas are malignant which was the case with our patient. We implemented complex complex combined approach in the treatment - surgical resection of the pancreatic lesion by distal pancreatectomy as well as bland and Chemoembolization of the metastasis to the liver. Also, we controlled the blood glucose by using Diazoxide, Prednisone and Octreotide with good results keeping the blood sugar in normal ranges by long term use of diazoxide.